2006
DOI: 10.1002/jor.20113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging and degeneration on disc volume and shape: A quantitative study in asymptomatic volunteers

Abstract: Debate continues on the effect of disc degeneration and aging on disc volume and shape. So far, no quantitative in vivo MRI data is available on the factors influencing disc volume and shape. The objective of this MRI study was to quantitatively investigate changes in disc height, volume, and shape as a result of aging and/or degeneration omitting pathologic (i.e., painful) disc alterations. Seventy asymptomatic volunteers (20-78 years) were investigated with sagittal T1-and T2-weighted MR-images encompassing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 34 publications
7
109
0
1
Order By: Relevance
“…Association between intervertebral disc degeneration and DS remained controversial. Decreased intervertebral disc height, or narrowing was usually considered as a degenerative indicator [7,19]. Some studies indicated that intervertebral disc narrowing had no significant relationship with DS [5,20].…”
Section: Discussionmentioning
confidence: 99%
“…Association between intervertebral disc degeneration and DS remained controversial. Decreased intervertebral disc height, or narrowing was usually considered as a degenerative indicator [7,19]. Some studies indicated that intervertebral disc narrowing had no significant relationship with DS [5,20].…”
Section: Discussionmentioning
confidence: 99%
“…1 were measured in a healthy cadaveric lumbar disc (Grade = 2.3) [25]. T1 was measured at both 7T and 3T magnetic field strength using a fully relaxed (TR = 5,100 ms) 2D spin echo inversion recovery pulse sequence with ten different inversion times (TI = 33-5,000 ms, TE = 11/13 ms (7T and 3T, respectively), in-plane resolution = 200 9 200 lm 2 , slice thickness = 5 mm, matrix = 256 9 256, and field of view = 5.1 9 5.1 cm 2 , Receiver Bandwidth (RBW) = 200 Hz/Px).…”
Section: Optimization Of Cep Image Contrastmentioning
confidence: 99%
“…While for some subjects 2-3 levels were used from a single spine, consistent with common practice in the literature [32][33][34], these discs were assumed to be independent samples and post hoc statistical analysis confirmed no subject dependence on CEP height. Each whole spine was first scanned with a mid-sagittal T2-weighted turbo spin echo imaging sequence for routine grading of degenerative state [25,26]. The integer grade from five individual examiners was averaged (Grade: 2.8 ± 0.7).…”
Section: Optimization Of Cep Image Contrastmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different small [39,48,60] and large animal models [27,37,44] have been described and reviewed in great detail [2,32], though no animal is identical to the human situation and each model has individual advantages and disadvantages, which should be carefully considered. The use of the minipig model is attractive because porcine spines are close to human anatomy, IVDs are almost as large as human discs [15,35,44,45,54] and it allows to test if the transplanted cells can survive in this relatively large biologic structure without vascular supply.…”
Section: Introductionmentioning
confidence: 99%